Report of three cases: congenital chylothorax and treatment modalities - (:unkn) unknown (TURKISH J PEDIATRICS, 2007)
Chylothorax is the most common cause of pleural effusion in the newborn. We report three patients with congenital chylothorax and discussed the clinical course and treatment options. Cases 1 and 2 with congenital chylothorax were treated by chest tube placement and total parenteral nutrition (TPN), and were fed a formula rich in medium-chain triglyceride. They were discharged home without any sequelae. Our 3(rd) case with chylothorax did not respond to the conventional therapies. Octreotide infusion was tried without any benefits and necessitated surgical intervention, but the infant developed chronic lung disease requiring nasal oxygen therapy until three months of age. All three patients developed complications of chylothorax treatment like chest tube dysfunction, pneumothorax, nosocomial sepsis, and cholestasis. Management of congenital chylothorax necessitates a multidisciplinary approach. Treatment options include pleural drainage, cessation of enteral feeding and initiation of TPN. Experience with octreotide treatment is limited. Surgery should be reserved for severe and refractory cases.
Keywords: congenital chylothorax; newborn; octreotide; pleurodesis; MANAGEMENT; CHILDREN